2021
DOI: 10.3389/fimmu.2021.775168
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Pre-Eclampsia, and Complement System

Abstract: COVID-19 is characterized by virus-induced injury leading to multi-organ failure, together with inflammatory reaction, endothelial cell (EC) injury, and prothrombotic coagulopathy with thrombotic events. Complement system (C) via its cross-talk with the contact and coagulation systems contributes significantly to the severity and pathological consequences due to SARS-CoV-2 infection. These immunopathological mechanisms overlap in COVID-19 and pre-eclampsia (PE). Thus, mothers contracting SARS-CoV-2 infection d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 221 publications
(271 reference statements)
0
21
0
Order By: Relevance
“…Previous studies have shown that antibodies produced by mothers infected with COVID-19 pass through the placenta to the fetus [8,9]. Although the risk and symptoms of pregnant women infected with COVID-19 are the same as those of non-pregnant people [10,11], several studies have found that, compared with age-matched non-pregnant women, pregnant women are more likely to have severe symptoms after being infected with COVID-19, especially when combined with risk factors such as advanced age, preeclampsia, obesity, diabetes, and high blood pressure [11][12][13]. The risk of neonatal complications such as premature delivery, meconium staining, respiratory distress, and perinatal death increases as well [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that antibodies produced by mothers infected with COVID-19 pass through the placenta to the fetus [8,9]. Although the risk and symptoms of pregnant women infected with COVID-19 are the same as those of non-pregnant people [10,11], several studies have found that, compared with age-matched non-pregnant women, pregnant women are more likely to have severe symptoms after being infected with COVID-19, especially when combined with risk factors such as advanced age, preeclampsia, obesity, diabetes, and high blood pressure [11][12][13]. The risk of neonatal complications such as premature delivery, meconium staining, respiratory distress, and perinatal death increases as well [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk and symptoms of pregnant women infected with COVID-19 are the same as those of non-pregnant people [10,11], several studies have found that, compared with age-matched non-pregnant women, pregnant women are more likely to have severe symptoms after being infected with COVID-19, especially when combined with risk factors such as advanced age, preeclampsia, obesity, diabetes, and high blood pressure [11][12][13]. The risk of neonatal complications such as premature delivery, meconium staining, respiratory distress, and perinatal death increases as well [12][13][14][15][16][17][18][19][20]. According to the characteristics of different COVID-19 vaccines, the components in the mRNA vaccine would not enter the nucleus of the host cell and remain separated from the host DNA.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the constant deposition of C3b generates the C5 convertase, which signals its cleavage to elements C5a and C5b (anaphylatoxins). C5b then binds to C6, C7, and multiple molecules of C9, forming the terminal complement complex C5b-9, known as the “membrane attack complex” (MAC) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The complement system seems to be fundamental in the inflammatory process of PE and HELLP syndrome, with various studies demonstrating that PE is eventually a complement-mediated disease ( Figure 1 ). Elevated amounts of complement components and their activation derivatives, including C5a, and C5b-9 complex, have been detected in the circulation of PE patients compared to uncomplicated pregnancies, albeit the data in this field are highly contradictory [ 25 ]. Complement activation products were also discovered in the urine of severe PE patients and are thought to be a sign of complement-mediated kidney injury [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation